REARING OF TWO ENTOMOPATHOGENIC NEMATODES, Heterorhabditis bacteriophora Poinar AND Steinernema sp. IN TERMITE (Odontotermes obesus Ramb.) (Applied Biological Research, 2018)
The in vivo methods for rearing of entomopathogenic nematodes requires large quantities of insect hosts like greater wax moth, Galleria mellonella (L.) which  involves more time and additional costs, necessitates alternative host for  multiplication of entomopathogenic nematodes. The present study was aimed  to assess the infectivity and multiplication of two entomopathogenic nematodes, Heterorhabditis bacteriophora Poinar and Steinernema sp. isolated from Majuli  river island of Assam in subterranean termiteOdontotermes obesus (Ramb). The laboratory tests using Petri-dishes, illustrated the effectiveness of both the  nematodes against O. obesus at 100 IJs termite-1(worker/soldier) within 24-48  h, in which the nematodes could reproduce in 5-7 days. The natural mounds  (250 g) containing O. obesus (80-100 workers/ soldiers/nymphs) were also  inoculated with H. bacteriophora and Steinernema sp. at 1000 IJs and incubated  at room temperature (30±2oC) up to 20 days for multiplication. Following the  Cobb decanting and sieving method, the results exhibited the optimum yields  of 30,000 and 25,000 IJs of H. bacteriophora and Steinernema sp., respectively,  at 15 days beyond which the IJs starts deterioration. Under laboratory  condition entomopathogenic nematodes H. bacteriophora and Steinernema sp.  can be reared and mass produced for further management practices against  termite.
Keywords: Entomopathogenic nematodes; Heterorhabditis bacteriophora; rearing; mass culture; Steinernema sp